DESAIN MODEL RELASIONAL DATA TARGET COSTING SYSTEM - Mokhammad Mastotok Illah (Universitas Merdeka Malang, 2017)
This study aims to design an information system that can support research implementation of target costing system with Data Analysis Program, to design the Program Data analysis in research, analyse the effectiveness of the program to be used and evaluate the weakness and superiority of the program will come. In this study the authors use the questionnaire distribution tool Design Model Relational Data Target Costing System, for the purpose of research can be achieved more accurately. In designing the design of Target Costing questionnaire to the built system shows that the Target Costing questionnaire that has been designed is useful to provide an information system that can generate output (output) and input (entry, edit, inquiry, add record), based on the input query According to the required researcher needs related to the target costing. Access program as a tool to design, create tables, create forms and create reports. To display accurate results, then by designing the Target Costing questionnaire, can display data that produces graphs, reports, queries or filter data with Filter by Form to facilitate the search data in accordance with the needs of researchers. DOI: https://doi.org/10.26905/jtmi.v3i2.1323